CNS Remyelination and the Innate Immune System - McMurran, Christopher E.; Jones, Clare A.; Fitzgerald, Denise C.; Franklin, Robin J. M. (Frontiers in Cell and Developmental Biology, 2016)
A misguided inflammatory response is frequently implicated in myelin damage. Particularly prominent among myelin diseases, multiple sclerosis (MS) is an autoimmune condition, with immune–mediated damage central to its aetiology. Nevertheless, a robust inflammatory response is also essential for the efficient regeneration of myelin sheaths after such injury. Here, we discuss the functions of inflammation that promote remyelination, and how these have been experimentally disentangled from the pathological facets of the immune response. We focus on the contributions that resident microglia and monocyte-derived macrophages make to remyelination and compare the roles of these two populations of innate immune cells. Finally, the current literature is framed in the context of developing therapies that manipulate the innate immune response to promote remyelination in clinical myelin disease.